Research contributions on childhood obesity from a public-private partnership - Perry, Cheryl L (Int J Behav Nutr Phys Act, 2015)
BACKGROUND: Childhood obesity remains a significant global problem with immediate and long-term individual health and societal consequences. Targets for change should include the most potent and predictive factors for obesity at all levels of the personal, social and physical environments. The Michael & Susan Dell Center for Healthy Living (‘the Center’) is a public-private partnership that was developed to address child health issues through research, service, and education. This overview paper introduces a special issue of seven articles on childhood obesity from the Center, and the implications of this research for obesity prevention. METHODS AND RESULTS: A review of the literature on public-private partnerships was undertaken and key components of the partnership between the Michael & Susan Dell Foundation and the Center were compared for compatibility. The conceptual framework for Center research, based on social cognitive theory and the social-ecological model, is explained. An overview of papers in this special issue, relative to the conceptual framework, and the implications of this research for childhood obesity prevention, are provided. CONCLUSIONS: The public-private partnership that created the Michael & Susan Dell Center for Healthy Living has been instrumental in motivating the Center’s academic faculty to focus their research on improvements in child, family and community health through etiologic, epidemiologic, methodologic and intervention research. This special issue extends this work and places particular emphasis on socioeconomic inequalities in addressing the obesity problem in the U.S. and worldwide.